Intraoperative radiotherapy for primary and recurrent rectal cancer - Kallinowski, Friedrich; Eble, Michael J.; Buhr, Heinz J.; Wannenmacher, Michael; Herfarth, Christian (European journal of surgical oncology, 1995)
A total of 40 primary and 20 recurrent adenocarcinomas of the rectum were treated. Intraoperative radiation therapy was combined with pre- or postoperative irradiation and 5-FU and leucovorin treatment. An abdomino-perineal excision was performed in 32 and an anterior resection in 26 cases. A Hartmann's procedure was performed in two patients. Forty-two tumours were completely resected. Residual disease was microscopically detectable in 10 cases. In eight patients, tumour residual was evident macroscopically. Postoperatively, wound infection was observed in six and anastomotic dehiscence in four cases. After a follow-up of 20 months, 46 patients revealed no evidence of disease. Local recurrences and distant metastases were detected in two patients each. Ten patients died of their disease.